2002
DOI: 10.3390/s21100436
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Modelling of the Electrode Process of Azithromycin Using Cyclic Voltammetry at Hanging Mercury Drop Electrode

Abstract: Abstract:A theoretical treatment is presented to predict the kinetic behaviour of azithromycin at the surface of hanging mercury drop electrode using cyclic voltammetry. A model is developed to incorporate the occurrence of adsorption of the oxidized and reduced species of azithromycin at the surface of mercury drop electrode. An analytical solution was obtained using MATHEMATICA Wolfram Research, Inc.) to predict the cyclic voltammetric profiles by calculating the currents resulting after applying variable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…According to data from Fig. 8 , oxidation potential is decreased by increasing pH, which shows the participation of proton in the oxidation mechanism process of Azi as reported previously (Shawabkeh and Tutunji 2002 ). Also, the highest peak current was observed at pH 7.0, which was the optimum pH for electrochemical analysis (Fig.…”
Section: Resultssupporting
confidence: 85%
“…According to data from Fig. 8 , oxidation potential is decreased by increasing pH, which shows the participation of proton in the oxidation mechanism process of Azi as reported previously (Shawabkeh and Tutunji 2002 ). Also, the highest peak current was observed at pH 7.0, which was the optimum pH for electrochemical analysis (Fig.…”
Section: Resultssupporting
confidence: 85%
“…The various pH also affected the potential of AZM oxidation, shifting toward negative directions at higher pH. This shift suggests the participation of H + in the oxidation of AZM [27] . The proposed mechanism of AZM oxidation is shown in Scheme 1, in which the amine group from N3 (red) is oxidized and the dialkylamine experiences further oxidation, leading to the formation of a radical cation upon losing a single electron.…”
Section: Resultsmentioning
confidence: 99%
“…This shift suggests the participation of H + in the oxidation of AZM. [27] The proposed mechanism of AZM oxidation is shown in Scheme 1, in which the amine group from N3 (red) is oxidized and the dialkylamine experiences further oxidation, leading to the formation of a radical cation upon losing a single electron. This radical cation manifests as the oxidation peak current of AZM.…”
Section: Effect Of Optimum Phmentioning
confidence: 99%
“…The figure revealed two peak potentials for the signalling of AN, i. e. 850 mV and 1150 mV. It has previously been reported that AN oxidizes at a potential of 1181 mV . At low concentrations (7–15 nmol/L AN) the first peak potential shifts anodically with increase in AN concentration from 900 mV to 925 mV.…”
Section: Resultsmentioning
confidence: 99%